Effect of electrospun nanofibres and MWCNTs on the low velocity impact response of carbon fibre laminates. (15th February 2020) - Sarasini, Fabrizio; Tirillò, Jacopo; Bavasso, Irene; Bracciale, Maria Paola; Sbardella, Francesca; Lampani, Luca; Cicala, Gianluca
Abstract: The effects of electrospun veil position, areal density and concurrent presence of MWCNTs on the low velocity impact behaviour and damage tolerance of thin cross-ply carbon/epoxy laminates were investigated. Three different interleaved configurations were tested along with baseline laminates and the optimal configuration was then used to assess the effect of veil density (1.5 gsm and 4.5 gsm) and CNT doping on the damage tolerance. The presence of nanofibrous interlayers resulted in a decrease higher than 40% in the delaminated area for impacts up to 7.5 J without weight penalty and degradation of the in-plane flexural properties. SEM micrographs of fractured surfaces allowed to identify the synergistic contribution of MWCNTs and nanofibres to the effective toughening of traditional laminates. Energy absorption mechanisms were found similar to those described in fracture toughness studies, which resulted in a better damage tolerance of modified laminates in terms of residual flexural strength and stiffness.